Recent Trends in Endoscopic Bariatric Therapies - Hyuk Soon Choi; Hoon Jai Chun (Korean Society of Gastrointestinal Endoscopy, 2017)
Obesity and its associated metabolic diseases including diabetes mellitus are severe medical problems that are increasing in prevalence worldwide and result in significant healthcare expenses. While behavioral and pharmacological treatment approaches are partly effective in the short term, their effects are not long-lasting. Although previous studies have described bariatric surgery as the most effective treatment for obesity, it is associated with morbidity, mortality, and economic burden. Endoluminal interventions performed entirely using gastrointestinal flexible endoscopy offer alternative approaches to the treatment of obesity that are safer and more cost-effective than current surgical approaches. The use of endoluminal techniques in the field of metabolic obesity disease has diverse promising applications including endoscopic gastroplasty, intragastric balloon, endoluminal malabsorptive bariatric procedures, and gastric electrical stimulation (GES) for the modulation of gastric emptying. This review discusses recent trends and roles in endoscopic bariatric therapies using the currently available endoluminal and transgastric technologies.